Perianal warty dyskeratoma - Mohammed, Otarid B.; Kadori, Waad I.; Ebrahim, Ebrahim; Gwea, Ahmed; Telfah, Hussam; Karzoun, M. Zaki (International Journal of Research in Dermatology, 2024)
Warty dyskeratoma is a rare keratinization disorder marked by acantholytic dyskeratosis and belongs to the spectrum of acantholytic dyskeratosis in dermatology. It was first documented in 1954 and typically manifests in the head, neck, oral mucosa, and trunk, with several cases reported since its discovery. A 35-year-old unmarried gentleman presented in April 2022 with a 5-year history of perineal itching and discomfort. His physical examination revealed a 7-8 centimeter perianal grouped papular plaque. His medical history was unremarkable, and he has no family history of similar conditions or other dermatological disorders. Lab results showed non-reactive rapid plasma reagin and human immunodeficiency antigen/antibody combo. Liver and renal function tests were within normal range as well. The microscopic findings revealed features including prominent hyperkeratosis, invagination filled with keratin, and the surrounding area exhibiting acantholysis and intercellular edema. In conjunction with the patient’s clinical presentation, this histological profile led to the diagnosis of warty dyskeratoma. After treatment with calcipotriene and other topical agents, the last presentation showed very good improvement; the physical examination indicated remarkable thin, flat, soft, grayish plaque in the perianal area. This case report presents a unique instance of warty dyskeratoma affecting the perianal area, shedding light on differential diagnosis and clinical management in this atypical context, which significantly broadens the understanding and emphasizing that the Warty dyskeratoma can manifest in diverse body regions, urging its consideration in the differential diagnosis of perianal papular lesions.